Fundamentos de Chimú como estado - Aquise Caloapaza, Luis Fernando (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
This essay shows that Chimú is a State, but what is a State? therefore, it is a politically organized society directed by a ruling class and whose purpose is to achieve the common welfare of the population that is settled in a certain territory. In this sense, the State is made up of three essential elements: Power, People and Territory. Therefore, the Chimú State -discovered by Max Uhle in 1902-complies with the three fundamental elements. As for the territory, it included the entire north coast of Peru from Tumbes to the Chillón River, being its capital Chan Chan, from there power was exercised through the "Ciquic" or maximum Chimú rulers and in the surrounding valleys through the "Alaec", both were in charge of organizing and directing the human element -the town-that was dedicated to various economic activities such as fishing, crafts, goldsmithing, agriculture, etc., which allowed the subsistence and development of all the Chimu state.